Laparoscopic technique of modified extraperitoneal (retrotransversalis) end colostomy for abdominoperineal excision. (23rd July 2018) - Tulina, I. A.; Kitsenko, Yu. E.; Ubushiev, M. N.; Efetov, S. K.; Wexner, S. D.; Tsarkov, P. V.
Abstract: Aim: To describe the technique of a modified extraperitoneal retrotransversalis end colostomy as part of a laparoscopic abdominoperineal excision (APR). Method: The colostomy site is preoperatively chosen and used intra‐operatively for a trocar. After the rectum has been mobilized the descending colon is freed. The peritoneal margin is gently grasped and the parietal peritoneum and extraperitoneal together with the transversalis fascia are separated from the transverse abdominal muscle fibres upwards for 3–4 cm aiming at the trocar site to form the extraperitoneal retrotransversalis canal. The stoma site trocar is partially withdrawn and its head is turned laterally until its tip is positioned in the layer between the abdominal wall muscles and underlying transversalis and extraperitoneal fascia together with the parietal peritoneum. The CO2 source can be attached so that the gas helps to separate the layers, after which the colostomy trephine is formed at the site of the trocar, the grasper is inserted to gently deliver the blunt end of the descending colon through the canal and the end colostomy is formed in a usual way. Results: No procedure‐specific complications were noted in 39 patients who had laparoscopic APR with extraperitoneal retrotransversalis end colostomy from 2009 to 2016. In 23 patients who survived for 3.7 ± 1.7 years after surgery there were no clinical or CT signs of parastomal hernia or prolapse. Conclusion: This single‐institution retrospective case series demonstrates that laparoscopic extraperitoneal retrotransversalis end colostomy is feasible, safe and effective in preventing parastomal hernias and stomal prolapse.